Starting point 1979-1996 - Miyazaki, Hayao 1941- (VIZ Media, 2009)
Starting Point: 1979-1996 is a collection of essays, interviews, and memoir that go back to the roots of Miyazaki's childhood, the formulation of his theories of animation, and the founding of Studio Ghibli
Originally published: Japan, Studio Ghibli Inc., 1996. Unedited English translation, c2009
Keywords: Miyazaki, Hayao / 1941-; Miyazaki, Hayao / 1941- / Interviews; Miyazaki, Hayao; Animators / Japan / Biography; Animation (Cinematography) / Japan; Zeichentrickfilm; Biografie